Adornment Features of Nighties Preferred By Ladies: Exploring Ladies' Preference Towards Nightie Adornment Features (Journal of Advances and Scholarly Researches in Allied Education, 2013)
All human being adopted clothes to adorn their bodies bythe self-decoration to attract and impress other people. In this modern age,increased level of the dress consciousness of individuals has contributed tothe development of innovative designs, because it is the most important factorin consume choice of clothes. Therefore, this study was undertaken to determine thelady’s preference towards adornment features of nighties. In this study wasset-up is for nighties more and more women were getting engaged in differentprofessions outside their homes. Having to perform the dual duties of thehousehold as well as of the job. In the present set-up more women wereincreasingly becoming educated and socially alert. There is visible change inthe attitude of women towards their personal wardrobes. Since remain busythroughout the day, they usually prefer comfortable night clothes, not only torelax their tired bodies but also their tense nerves.